Oral Health Status in Patients with Fixed Orthodontic Appliance with Molar Bands and Bonded Tubes - Shrestha, Sandhya; Sharma, Anuj Kumar; Lamichhane, Bikash (Orthodontic Journal of Nepal, 2016)
Introduction: Studies on effect of orthodontic treatment on oral health are found in ample and have demonstrated a causeeffect relationship. Many comparative studies on molar bands and bonded tubes have shown that, former are detrimental for periodontal health. However there are evidences of bonded molar tubes with high failure rates and causative of gingivitis. Objective: To assess the effect of molar bands and bonded tubes on periodontal health of the Nepalese orthodontic patients. Materials & Method: A total of 112 orthodontic patients aged between 13-30 years were assessed for Plaque Index, Gingival Index, Calculus Index and pocket depth on upper first molars with cemented bands and bondable tubes. Statistical analysis was done using Chi-square test to find the association between cemented molar bands and bonded molar tubes to periodontal status. Level of significance was set at p<0.05. Result: Very few orthodontic patients showed poor plaque accumulation sore, severe gingivitis and calculus deposits. Contrarily, 17% patients showed deeper periodontal pockets. The Gingival Index showed significant association between cemented molar band and bonded molar tube groups (p=0.001). Conclusion: Oral health is an important concern in fixed orthodontic patients. Use of both molar band and molar tube can cause progression of gingivitis. There is no significant change in periodontal health parameters in using cemented bands or bonded tubes when the oral hygiene is controlled. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.27-31